Liquid calorimeters for measuring the energy of high-power microwave pulses; Instruments and Experimental Techniques; Vol. 58, iss. 4 - Vykhodtsev P. V. Pavel Vasiljevich; El'chaninov A. A. Anton Aleksandrovich; Klimov A. I. Aleksey Ivanovich; Koval’chuk O. B. Oleg Borisovich; Totmeninov E. M. Evgeny Markovich (2015, 2015)
Title screen